A Streamlined Sample Preparation Method for Mass Spectrometric Analysis. Issue 1 (9th April 2018) - Xiong, Yun; Zhang, Ying; Yao, Jun; Yan, Guoquan; Lu, Haojie
Abstract: Mass spectrometry‐based proteomic technology experienced remarkable advancement in the past decades. However, their application was still hampered by the complexity of sample preparation. Conventional strategies for sample preparation incorporate multiple time‐consuming steps, including cell lysis, protein extraction, protease cleavage, and desalting. Thus, we explored a simplified method (the cell‐absorb method) during which living cells were absorbed into vacuum‐dried polyacrylamide gel and directly digested in gel into peptides for subsequent LC‐MS/MS analysis. As a consequence, both of the steps for cell lysis and protein extraction involved in traditional protocol were skipped. In addition to the decrease in time, more proteins were identified. Indeed, 3022 proteins were identified by the cell‐absorb method. Meanwhile, only 2642 and 2420 proteins were identified by the classical SDS‐PAGE based method and the reported gel absorption‐based method, respectively. The cell‐absorb method exhibited apparent advantage in terms of the depth of proteome coverage. Furthermore, the number of proteins identified show excellent reproducibility with a CV (coefficient of variation) of 0.03 among three replicates using the cell‐absorb method. These advantages suggest that cell‐absorb method is a promising choice for mapping the whole proteome of cells. © 2018 by John Wiley & Sons, Inc.